Enhanced Energy Transfer in Quasi‐Quaternary Nanocrystal Superlattices. (19th December 2013) - Cargnello, Matteo; Diroll, Benjamin T.; Gaulding, E. Ashley; Murray, Christopher B.
<x xml:space="preserve">Abstract</x> Quasi‐quaternary nanocrystal superlattices are assembled by using exclusively core‐shell particles as building blocks. The assemblies show an enhancement of energy‐transfer from cadmium selenide‐based core‐shell quantum dots to gold‐iron oxide core‐shell nanocrystals compared to random mixtures of the same components. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>